Demography and genetics suggest reversal of dolphin source‐sink dynamics, with implications for conservation. Issue 3 (13th November 2018) - Manlik, Oliver; Chabanne, Delphine; Daniel, Claire; Bejder, Lars; Allen, Simon J.; Sherwin, William B.
Abstract: The forecast for the viability of populations depends upon metapopulation dynamics: the combination of reproduction and mortality within populations, as well as dispersal between populations. This study focuses on an Indo‐Pacific bottlenose dolphin ( Tursiops aduncus ) population in coastal waters near Bunbury, Western Australia. Demographic modeling of this population suggested that recent reproductive output was not sufficient to offset mortality. Migrants from adjacent populations might make up this deficit, so that Bunbury would act as a "sink, " or net recipient population. We investigated historical dispersal in and out of Bunbury, using microsatellites and mitochondrial DNA of 193 dolphins across five study locations along the southwestern Australian coastline. Our results indicated limited gene flow between Bunbury and adjacent populations. The data also revealed a net‐dispersal from Bunbury to neighboring populations, with microsatellites showing that more than twice as many individuals per generation dispersed out of Bunbury than into Bunbury. Therefore, in historic times, Bunbury appears to have acted as a source population, supporting nearby populations. In combination with the prior finding that Bunbury is currently not producing surplus offspring to support adjacent populations, this potential reversal of source‐sink dynamics may have serious conservation implications for Bunbury and other populations nearby.